1981
DOI: 10.1210/jcem-53-2-412
|View full text |Cite
|
Sign up to set email alerts
|

Aromatization of Androstenedione by Human Adipose Tissue Stromal Cells in Monolayer Culture*

Abstract: Stromal cells and adipocytes were separated after collagenase treatment of adipose tissue obtained from women undergoing elective surgery, and these cells were used to study aromatization of [3H]androstenedione in vitro. Aromatization activity was estimated either 1) by determining the incorporation of tritium from [1-3H]androstenedione into [3H]water or else 2) by determining the formation of [3H]estrone (E1) and [3H]estradiol (E2) from [1,2,6,7-3H]androstenedione. It was established that only 13% of the arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
4

Year Published

1983
1983
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(162 citation statements)
references
References 22 publications
2
156
0
4
Order By: Relevance
“…Ovaries are the main sites of oestrogen synthesis in premenopausal non-pregnant women. However, after menopause, local synthesis of oestrogens in some tissues, including mammary tissue, acquires a special importance in mammary carcinogenesis (Ackerman et al, 1981;Pasqualini, 2004;Pasqualini and Chetrite, 2005;Suzuki et al, 2005). The local synthesis of oestrogens depends on the activity of different enzyme families (aromatase, sulfatases, etc) to transform androgens into oestrogens, as well as compounds of weak oestrogenic activity into more active forms.…”
Section: Discussionmentioning
confidence: 99%
“…Ovaries are the main sites of oestrogen synthesis in premenopausal non-pregnant women. However, after menopause, local synthesis of oestrogens in some tissues, including mammary tissue, acquires a special importance in mammary carcinogenesis (Ackerman et al, 1981;Pasqualini, 2004;Pasqualini and Chetrite, 2005;Suzuki et al, 2005). The local synthesis of oestrogens depends on the activity of different enzyme families (aromatase, sulfatases, etc) to transform androgens into oestrogens, as well as compounds of weak oestrogenic activity into more active forms.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase activity in C6 glioma cells was measured by the tritiated water release assay, based on the formation of tritiated water during aromatisation of an androgenic substrate such as [1b-3 H(N)]-androst-4-ene-3,17-dione (Ackerman et al, 1981). Glioma cells were seeded onto 60 Â 15 mm tissue culture dishes (2 Â 10 6 cells per dish) in DMEM/HAM F12 mixture supplemented with 10% FBS, 20 U ml À1 penicillin and 20 mg ml À1 streptomycin.…”
Section: Direct Measurement Of Cellular Aromatase Activitymentioning
confidence: 99%
“…3 These conversions, catalysed by 17b-hydroxysteroid dehydrogenase (17b-HSD) and cytochrome P450 arom (aromatase) respectively, have been demonstrated to occur in adipose tissue. 4,5 In adipose tissue, aromatase activity and mRNA is localised predominantly in preadipocytes. 5,6 Killinger et al 7 reported that there are regional differences in preadipocyte sex steroid production.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In adipose tissue, aromatase activity and mRNA is localised predominantly in preadipocytes. 5,6 Killinger et al 7 reported that there are regional differences in preadipocyte sex steroid production. In cultured preadipocytes derived from human subcutaneous abdominal and omental adipose tissue, the formation of androgens from androstenedione was 10-fold greater than the formation of estrone, whereas in adipose tissue from the buttock and thigh, the production of androgens and estrone from androstenedione was equivalent.…”
Section: Introductionmentioning
confidence: 99%